CSR should contribute to the national agenda in emerging economies - the "Chatterjee Model" - Bhaskar Chatterjee; Nayan Mitra (International Journal of Corporate Social Responsibility (JCSR), 2017)
Emerging economies face a plethora of social, economic and environmental issues. On the one hand, these have adverse effects that negatively impact the overall development of such economies; and on the other, they offer challenges which when addressed, help these economies to chart a course of integrated and inclusive growth, thus providing them with an opportunity for national development. India is no different. It has rural Bharat on one side that is steeped in illiteracy, poverty on the one hand and, a literate, rich, glitzy, corporate, urban India on the other; thereby fortifying the predicaments of an emerging nation. This paper, through an analysis of the socio-economic dilemmas and challenges of an emerging nation like that of India and scrutinizing the roles and responsibilities of Corporations to combat such a quandary through CSR, introduces the "Chatterjee Model," that urges, from a policy-maker's point of view, that CSR should contribute to the national agenda of a country, helping it to accelerate its transition from an emerging to a developed nation.
Keywords: 650; Chatterjee Model; Corporate Social Responsibility (CSR); National agenda; Emerging economies; India; Cycle of Conversion; Companies Act 2013; Schedule VII; CSR Implementation; Tata Housing; Development Company Limited